A Socio-Pragmatics Analysis Of Commisive Utterance Used In The Lord Of The Rings Novel: The Fellowship Of The Ring - Suparwati, Beni (2005)
This research is based on the socio-pragmatics approach with the commisive speech act as the scope of analysis. The source of the data is the dialogs in The Lord of The Rings Novel: The Fellowship of The Ring written by JRR. Tolkien. The data can be in the form of words, phrases, clauses, and sentences. The research is aimed at describing forms of commisive utterances, finding out the speaker's intention and the reasons of employing certain commisive utterances. To achieve these objectives, firstly the researcher classified the data based on certain characteristics to justify the forms of commisive utterances. The SPEAKING formula is employed to describe the context of the dialogs. It is also used for clarifying the reasons of employing certain commissive utterances. While to find out the speaker intention, she applies the speech act theory especially the theory of locution and illocution. The results of the research are that there are 3 forms of commisive utterances; imperative, interrogative, declaration. The intentions of the speaker are promising, offering, threatening. The reason of employing such commisive utterances are; showing power, softening utterances, showing solidarity.